Malaysian organisational efficiency – implementation of six sigma methodology (Kecekapan organisasi di Malaysia – pelaksanaan tatakaedah enam sigma) - Sivakumar Suppremaniam; Kanesan Muthusamy (Penerbit Universiti Kebangsaan Malaysia, 2011)
﻿The implementation of productivity tools in multinational companies is usually well documented. Two of the fundamental productivity methods used are waste elimination and variation reduction. The objective of this research is to identify the Critical Success Factors (CSFs) of six sigma methodology implementation in Malaysian Multinational Corporations (MNCs). This research used the method of exploratory survey conducted via online questionnaire. The survey was conducted among 22 MNCs in Malaysia which used six sigma methodology in their organisations. The list of 22 companies was retrieved from Internet search. Of the 22 companies surveyed, 20 returned their completed responses. The study concluded that Project/Process Assessment and Training/Awareness are the most significant factors in the successful implementation of six sigma. The results support the Null Hypothesis (H0) that the success of six sigma implementation in Malaysia is directly impacted on by the identified CSFs. This research finding provides the necessary foundation for local companies to adopt and to ensure the correct approach is used in implementing six sigma in their organisations.